Anti-trypanosomal antibodies in sequentially collected sera of N'Dama cattle under natural trypanosomiasis risk in The Gambia - Dwinger, R.H.; Grieve, A.S.; Jeannin, P.; Agyemang, K.; Faye, J. (ILCA/ILRAD, 1988)
Investigates the time of appearance and the persistence of antibodies in N'Dama cattle bitten by infected tsetse flies under controlled conditions, the serology of village animals exposed to natural trypanosomiasis risk and the time of appearance and duration of anti-trypanosomal antibodies through the monthly collection of serum samples from calves following birth.